Physical Activity and Mental Health Among Physicians in Tertiary Psychiatric Hospitals: A National Crosssectional Survey in China - Luo, Jin; Liu, Huanzhong; Liu, Yuanli; Jiang, Feng; Tang, Yi-Lang (Frontiers in Psychology, 2021)
This study aimed to examine the level of mental health and its correlates, particularly physical activity (PA) frequency, among physicians in tertiary psychiatric hospitals. In a national cross-sectional survey, 4520 physicians nested in 41 tertiary psychiatric hospitals from 29 provinces completed the online questionnaire. Their mean age was 38.5±8.6 years, and 41.86% of physicians were male. More than one-third (35.24%) of physicians reported no PA in the past month, and only 21.88% reported happiness. Only 55.15% and 58.10% of physicians reported normal status of depression and anxiety. In the adjusted multivariable ordinal logistic regression, higher PA frequency was associated with depression, anxiety, and happiness, except those who reported PA almost every day. Programs that aim to increase PA may promote the mental health of physicians in tertiary psychiatric hospitals.